An Investigation of the Possible Role of Platelet Fibrinogen in Thrombi Formation - Johnson, Shirley A; McKenna, James L (Thrombosis and Haemostasis, 1963)
We have prepared solid clots that could be fixed, sectioned and stained and studied histologically from a high concentration of washed platelets in buffered saline. Plasma fibrinogen is not required for a clot with structure to form. The possibility of packed platelets composing the head of mixed thrombi is evident if a small amount of thrombin can be formed and the microscopic appearance of such a structure documented. No clot retraction of platelet fibrin took place. The platelet-plasma clots prepared as controls in this study lysed very readily when streptokinase was incorporated into the clot while it was not possible to lyse the washed platelet clots in the conditions of the experiment. Neither clot could be lysed with fibrinolysin.